Molecular Pathological Markers Correlated With the Recurrence Patterns of Glioma - Ge, Shunnan; Shi, Yingwu; Zhu, Gang; Li, Songlun; Cai, Yaning; Ji, Peigang; Liu, Jinghui; Guo, Wei; Gong, Li; Lou, Miao; Feng, Fuqiang; Wang, Yuan; et al. (Frontiers in Oncology, 2021)
Purpose: Glioma is one of the most common tumors of the central nervous system, and many patients suffer from recurrence even after standard comprehensive treatment. However, little is known about the molecular markers that predict the recurrence patterns of glioma. This study aimed to demonstrate the correlations between molecular markers and glioma recurrence patterns, which included local/nonlocal recurrence and paraventricular/ nonparaventricular recurrence. Methods: Immunohistochemical techniques were used to assess the molecular markers of 88 glioma tissues following surgical resection. The recurrence patterns were divided into local recurrence, marginal recurrence, distant recurrence, multirecurrence and subarachniod recurrence, with the last four recurrence patterns being collectively called nonlocal recurrence. According to whether the recurrence invaded ventricles, the nonlocal recurrence patterns were divided into paraventricular and nonparaventricular recurrence. Then, we compared the different recurrence patterns and their clinical characteristics, focusing on the expression of molecular markers. Results: More patients in the nonlocal recurrence group received combined radiotherapy and chemotherapy than patients in the local recurrence group (p=0.019). Sex, age, extent of surgery, time to recurrence, tumor location, size and WHO grade were not different in the defined groups (P>0.05). Recurrent tumor volume and WHO grade were significantly different between the paraventricular and nonparaventricular recurrence groups (p=0.046 and 0.033). The expression of Ki-67, P53 and PCNA in the nonlocal recurrence group was significantly higher than that in the local recurrence group (p=0.015, 0.009 and 0.037), while the expression of S-100 in the nonlocal recurrence group was significantly lower than that in the local recurrence group (p=0.015). Cox regression indicated hazard ratio (HR) for high expression level of PCNA associated with non-local recurrence was 3.43 (95% CI, 1.15, 10.24) , and HR for high expression level of MGMT associated with paraventricular recurrence was 2.64 (95% CI, 1.15,6.08). Conclusions: Ki-67, P53, PCNA and MGMT might be important clinical markers for nonlocal recurrence and paraventricular recurrence.